Nigeria, absorbing the oil wealth - Bienen, Henry S.; Gersovitz, Mark. (London : Euromoney Publications, 1982)
In this paper, the discussion on Nigerian stability is grouped around these major concerns: the politics of social cleavage (ethnicity and class and equity issues), territorial and revenue allocation issues, party discipline, civil-military relations, and foreign policy.
Includes bibliographical references.
ne 12/04/2019
Ref.
Keywords: Economics; Nigeria